Synthesis and antimicrobial activity of some new diphenylamine derivatives - Arvind Kumar; Arun K Mishra (Wolters Kluwer Medknow Publications, 2015)
In search of new leads toward potent antimicrobial agent, an array of novel derivatives of 2-hydrazinyl -N-N, diphenyl acetamide has been synthesized from the chloroacetylation reaction of diphenylamine (DPA). For this, a series of DPA derivatives were prepared by replacing chlorine with hydrazine hydrate in alcoholic medium and 2-hydrazino-N, N-diphenylacetamide was synthesized. The 2-hydrazino-N, N-diphenylacetamide was further subjected to reaction with various aromatic aldehydes in presence of glacial acetic acid in methanol. The synthesized compounds were characterized by their IR, 1HNMR spectral data and elemental analysis. The compounds were screened for antibacterial and antifungal activity by cup plate method. 2-(2-Benzylidenehydrazinyl)-N, N-diphenylacetamide (A1); 2-(2-(3-methylbenzylidene) hydrazinyl)-N, N-diphenyl-acetamide (A5) and 2-(2-(2-nitrobenzylidine) hydrazinyl)-N, N-diphenyl-acetamide compounds (A7) showed significant antimicrobial as well as antifungal activity. Diphenylamine compounds may be explored as potent antimicrobial and antifungal compounds.